Polyolefin adhesive composition

By using an acid-modified polyolefin, a multifunctional polyisocyanate curing agent and an organic solvent, and a layer following the molding is arranged on the inner layer side of the aluminum foil, the problems of the lithium battery packaging material in electrolyte resistance and formability are solved, and excellent applicability and formability are achieved.

CN110234721BActive Publication Date: 2025-03-25TOYOBO MC CORP

Patent Information

Application Number
CN201880008954.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-05-29
Filing Date
2018-04-12
Publication Date
2025-03-25
Estimated Expiration
2038-04-12

AI Technical Summary

Technical Problem

The existing packaging materials for lithium batteries are not satisfactory in terms of electrolyte resistance and formability, and it is difficult to take into account both the applicable life and the electrolyte resistance. The polyolefin substrate is prone to heat shrinkage at high temperatures, affecting adhesion and formability.

Method used

By using an adhesive composition containing an acid modified polyolefin, a multifunctional polyisocyanate curing agent and an organic solvent, the forming properties of the laminated body are improved by placing a layer that can follow the elongation during forming on the inner layer side of the aluminum foil.

Benefits of technology

It achieves good applicability, adhesion, chemical resistance and formability, can maintain good performance of the adhesive under low temperature conditions, and reduce the influence of heat shrinkage at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0002147024580000141
    Figure GDA0002147024580000141
  • Figure GDA0002147024580000151
    Figure GDA0002147024580000151
  • Figure GDA0002147024580000171
    Figure GDA0002147024580000171
Patent Text Reader

Abstract

The present invention aims to provide an adhesive composition containing an acid-modified polyolefin and a polyfunctional polyisocyanate curing agent, which has good pot life, good adhesion between a metal substrate and a polyolefin resin substrate, good chemical resistance and good formability. An adhesive composition contains an acid-modified polyolefin (A), a polyfunctional polyisocyanate curing agent (B) and an organic solvent (C), wherein the acid value of the acid-modified polyolefin (A) is 2 to 50 mgKOH / g resin, and the ratio of acetone extractable components is 0.01 to 2 mass %.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition that exhibits good adhesion, chemical resistance, and formability between a polyolefin resin substrate and a metal substrate. More specifically, it relates to an adhesive composition containing an acid-modified polyolefin, a multifunctional polyisocyanate curing agent, and an organic solvent. In particular, it relates to an adhesive composition for lithium-ion batteries (hereinafter referred to as LiB), and a packaging material for a laminate containing the adhesive composition. Background Art

[0002] In recent years, ultra-thin and miniaturized LiBs have been actively developed as batteries for personal computers, mobile phones and other portable terminal devices, cameras, satellites, etc. The packaging materials of these LiBs are different from the metal cans used in the past. Due to the advantages of being lightweight and allowing the shape of the battery to be freely selected, laminates such as a base material layer / barrier layer / sealant layer are gradually being used.

[0003] LiB contains positive electrode materials and negative electrode materials, and also contains an electrolyte obtained by dissolving lithium salts in aprotic solvents such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, or an electrolyte layer composed of a polymer gel impregnated with the electrolyte as battery contents. If such a highly permeable solvent passes through the sealant layer, the stacking strength between the barrier layer and the sealant layer will be reduced, stratification will occur, and eventually problems such as electrolyte leakage will occur. In addition, as the electrolyte of the battery, that is, lithium salts, substances such as LiPF6 and LiBF4 are used, but these salts will produce hydrofluoric acid due to hydrolysis reaction with water, and hydrofluoric acid will corrode the barrier layer, thereby reducing the stacking strength. In this way, the battery packaging material needs to have tolerance to the electrolyte.

[0004] In addition, if LiB is used in various environments, it needs to have more stringent tolerance. For example, when used in mobile devices, it is required to be resistant to leakage in high temperature environments such as 60 to 70°C in cars. In addition, if it is used in a mobile phone and accidentally dropped into water, it also needs to be water-resistant so that water does not penetrate.

[0005] In view of such circumstances, various lithium battery packaging materials having improved electrolyte resistance have been proposed (see, for example, Patent Documents 1 to 3).

[0006] In addition, in the battery packaging material, a mold is used to form a space for accommodating the battery element when the battery element is enclosed. During this forming, the battery packaging material is stretched, which may cause cracks and pinholes in the barrier layer of the flange part of the mold. In particular, with the demand for smaller and thinner batteries in recent years, thinner battery packaging materials are being sought, and such problems are more likely to occur.

[0007] In view of such a situation, battery packaging materials having improved formability have been proposed (see, for example, Patent Documents 4 and 5).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2001-243928

[0011] Patent Document 2: Japanese Patent Application Publication No. 2004-42477

[0012] Patent Document 3: Japanese Patent Application Publication No. 2009-238475

[0013] Patent Document 4: Japanese Patent Application Publication No. 2002-216714

[0014] Patent Document 5: Japanese Patent Application Publication No. 2003-31188 Summary of the invention

[0015] Problems to be solved by the invention

[0016] However, the above-mentioned lithium battery packaging materials are not satisfactory in terms of electrolyte resistance and formability. In addition, even if the electrolyte resistance and formability are greatly improved, there are still problems.

[0017] Specifically, the following problems are observed: it is difficult to ensure both the applicability and electrolyte resistance of the adhesive after mixing the curing agent (Patent Document 1); since the bonding is performed by extrusion lamination, the lamination machine is restricted, or the polyolefin substrate is affected by thermal shrinkage due to lamination at high temperature (Patent Document 2); since the polyolefin main agent is water-based, the drying time is long and the production conditions are limited (Patent Document 3). In addition, not only is it necessary to set a process of coating an amide-based slip agent on the surface of the outer film, which reduces productivity, but also the lamination strength of the outer film and the aluminum foil cannot be fully obtained due to the coated amide-based slip agent (Patent Document 4); since the inner layer side of the aluminum foil is only configured with an unstretched polypropylene resin film, or the inner layer side of the aluminum foil is only configured with a film of a mixed resin of polypropylene and polyethylene, when formed into a rectangular shape, pinholes will be generated in the aluminum foil, or the aluminum foil is prone to fractures (cracks), and sufficient formability cannot be obtained (Patent Document 5), etc.

[0018] The present invention aims to provide an adhesive composition which has no problems such as shelf life and production conditions and has excellent adhesion, chemical resistance (electrolyte resistance) and formability. Furthermore, the present invention aims to provide a battery packaging material comprising an adhesive layer composed of the adhesive composition and a battery using the packaging material.

[0019] Means to solve the problem

[0020] In order to achieve the above-mentioned problems, the inventors of this case conducted intensive research and found that it is effective to configure a layer that can fully follow the elongation during molding not only on the outer layer side of the aluminum foil but also on the inner layer side, and proposed the following invention.

[0021] An adhesive composition comprises an acid-modified polyolefin (A), a multifunctional polyisocyanate curing agent (B) and an organic solvent (C), wherein the acid value of the acid-modified polyolefin (A) is 2 to 50 mgKOH / g resin, and the ratio of the acetone extractable component of the acid-modified polyolefin (A) is 0.01 to 2% by mass.

[0022] The acid-modified polyolefin (A) preferably contains 0.5 to 40 parts by mass of a polyfunctional polyisocyanate curing agent (B) and 80 to 2000 parts by mass of an organic solvent (C) relative to 100 parts by mass of the acid-modified polyolefin (A). In addition, the organic solvent (C) is preferably a mixed solution of a solvent (C1) and a solvent (C2), wherein the solvent (C1) is one or more solvents selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons and halogenated hydrocarbons, and the solvent (C2) is one or more solvents selected from the group consisting of alcohol solvents, ketone solvents, ester solvents and glycol ether solvents, and the solvent (C1) / solvent (C2)=50 to 97 / 50 to 3 (mass ratio).

[0023] The adhesive composition is preferably used for bonding a polyolefin resin substrate to a metal substrate.

[0024] A laminate of a polyolefin resin substrate and a metal substrate bonded by the adhesive composition; and a lithium ion battery packaging material using the laminate as a constituent member.

[0025] Effects of the Invention

[0026] The adhesive composition of the present invention contains an acid-modified polyolefin, a multifunctional polyisocyanate curing agent and an organic solvent, and does not increase viscosity or gel even when stored for a long period of time, and can maintain a good shelf life. Furthermore, even if the adhesive composition is bonded at a low temperature of 120°C or less, which has little effect on the thermal shrinkage of the polyolefin substrate, or is aged at a low temperature of 40°C or less, it can still have good adhesion and chemical resistance with the polyolefin resin substrate and the metal substrate, and can also have good formability.

[0027] According to the present invention, a good pot life can be maintained, and the adhesive layer can be fully cured by the aging process after lamination, and can exhibit excellent adhesion and chemical resistance. Furthermore, an adhesive layer having storage modulus and elongation at break required to exhibit excellent formability can be obtained. DETAILED DESCRIPTION

[0028] Hereinafter, embodiments of the present invention will be described in detail.

[0029] <Acid-modified polyolefin (A)>

[0030] The acid-modified polyolefin (A) used in the present invention has an acid value of 2 to 50 mgKOH / g-resin and an acetone extractable component ratio of 0.01 to 2% by mass.

[0031] The acid-modified polyolefin (A) used in the present invention is not limited, but is preferably one obtained by grafting at least one of α,β-unsaturated carboxylic acid and its anhydride to at least one of polyethylene, polypropylene and propylene-α-olefin copolymer.

[0032] The propylene-α-olefin copolymer is a copolymer obtained by copolymerizing α-olefin with propylene as the main component. As the α-olefin, for example, one or more of ethylene, 1-butene, 1-heptene, 1-octene, 4-methyl-1-pentene, vinyl acetate, etc. can be used. Among these α-olefins, ethylene and 1-butene are preferred. Although the ratio of the propylene component to the α-olefin component of the propylene-α-olefin copolymer is not limited, it is preferred that the propylene component is 50 mol% or more, and more preferably 70 mol% or more.

[0033] As at least one of the α,β-unsaturated carboxylic acids and their anhydrides, for example, maleic acid, itaconic acid, citraconic acid and their anhydrides can be cited. Among these, anhydrides are preferred, and maleic anhydride is more preferred. Specifically, maleic anhydride-modified polypropylene, maleic anhydride-modified propylene-ethylene copolymer, maleic anhydride-modified propylene-butene copolymer, maleic anhydride-modified propylene-ethylene-butene copolymer, etc. can be cited. These acid-modified polyolefins can be used alone or in combination of two or more.

[0034] From the viewpoint of adhesion and electrolyte resistance between the polyolefin resin substrate and the metal substrate, the acid value of the acid-modified polyolefin (A) needs to be in the range of 2 to 50 mgKOH / g resin. Preferably, it is in the range of 3 to 45 mgKOH / g resin, more preferably 5 to 40 mgKOH / g resin, and particularly preferably in the range of 7 to 35 mgKOH / g resin. When it is less than the above value, there is sometimes a lack of compatibility with the curing agent. Therefore, sometimes there is a low crosslinking density, reduced bonding strength, and reduced chemical resistance (electrolyte resistance). When it exceeds the above value, due to the low molecular weight and weak cohesion, sometimes there is a decrease in bonding strength and chemical resistance (electrolyte resistance). Further, the manufacturing efficiency will also be reduced, so it is not preferred.

[0035] The acid value of the acid-modified polyolefin (A) can be adjusted by adjusting the amount of the α,β-unsaturated carboxylic acid, the anhydride of the α,β-unsaturated carboxylic acid, and the radical generator used.

[0036] Based on the adhesion between the polyolefin resin substrate and the metal substrate and the electrolyte resistance, the acetone extraction component ratio of the acid-modified polyolefin (A) must be in the range of 0.01% to 2% by mass. It is preferably 0.03% to 1.7% by mass, more preferably 0.05% to 1.4% by mass, further preferably 0.07% to 1.2% by mass, and particularly preferably 0.1% to 1% by mass. When it is less than the above value, the manufacturing efficiency is reduced, so it is not preferred. When it exceeds the above value, there is a situation where the cohesion is weakened, the adhesion, chemical resistance and formability are poor.

[0037] Based on the adhesion and chemical resistance (electrolyte resistance) between the polyolefin resin substrate and the metal substrate, the storage modulus (E') of the acid-modified polyolefin (A) at 25°C is preferably in the range of 10 to 2000 MPa. More preferably, it is 15 to 1700 MPa, further preferably 20 to 1400 MPa, particularly preferably 25 to 1100 MPa, and most preferably in the range of 30 to 800 MPa. When it is less than the above value, there will be a situation where the cohesion of the adhesive layer composed of the adhesive composition is insufficient, and the adhesion and chemical resistance (electrolyte resistance) are poor. When the above value is exceeded, the followability of the adhesive layer composed of the adhesive composition is reduced, and the adhesion is poor. In addition, if it is within the above range, since the adhesion and substrate followability are improved, the formability of the laminate is also improved, so it is more preferred as a packaging material for lithium ion batteries.

[0038] The tensile elongation at break (Eb) of the acid-modified polyolefin (A) at 25°C is preferably in the range of 50% to 1000%. It is more preferably 80% to 900%, further preferably 120% to 800%, particularly preferably 160% to 700%, and most preferably 200% to 600%. When it is less than the above value, the followability of the adhesive layer composed of the adhesive composition is reduced, causing pinholes during molding, etc., and the formability is poor. In addition, in general, the tensile elongation at break (Eb) and the storage modulus (E') are opposite properties. When the above value is exceeded, the storage modulus (E') becomes low, and the adhesion and electrolyte resistance are poor. In addition, if it is within the above range, since the adhesion and substrate followability are improved, the formability of the laminate is also improved, so it is more preferred as a packaging material for lithium ion batteries.

[0039] The weight average molecular weight (Mw) of the acid-modified polyolefin (A) is preferably in the range of 10,000 to 200,000. It is more preferably in the range of 20,000 to 180,000, further preferably in the range of 30,000 to 160,000, particularly preferably in the range of 40,000 to 140,000, and most preferably in the range of 50,000 to 110,000. When it is less than the above value, there is a case where the cohesive force becomes weak and the adhesion is poor. On the other hand, when it exceeds the above value, there is a case where the fluidity is low and the operability during bonding is problematic. If it is within the above range, the curing reaction with the curing agent is effectively utilized, so it is preferred.

[0040] The crystallinity of the acid-modified polyolefin (A) means that the acid-modified polyolefin (A) shows a clear melting peak in the process of heating from -100°C to 250°C at 20°C / min using a differential scanning calorimeter (DSC).

[0041] The acid-modified polyolefin is advantageously crystalline because it has stronger cohesive force than an amorphous polyolefin and has excellent adhesiveness and chemical resistance.

[0042] The melting point (Tm) of the acid-modified polyolefin (A) is preferably in the range of 50°C to 120°C. It is more preferably in the range of 60°C to 100°C, and most preferably in the range of 70°C to 90°C. When it is less than the above value, the cohesive force derived from crystallization may be weakened, and the adhesiveness and chemical resistance may be poor. On the other hand, when it exceeds the above value, the solution stability and fluidity may be low, and the workability during bonding may be problematic.

[0043] The heat of fusion (ΔH) of the acid-modified polyolefin (A) is preferably in the range of 1 J / g to 60 J / g. It is more preferably in the range of 3 J / g to 50 J / g, and most preferably in the range of 5 J / g to 40 J / g. When it is less than the above value, the cohesive force derived from crystallization may be weakened, and the adhesiveness and chemical resistance may be poor. On the other hand, when it exceeds the above value, the solution stability and fluidity may be low, and the workability during bonding may be problematic.

[0044] The method for producing the acid-modified polyolefin (A) is not particularly limited, and examples thereof include a radical graft reaction (i.e., a reaction in which a radical species is generated for a polymer serving as a main chain and an unsaturated carboxylic acid and an acid anhydride are graft-polymerized using the radical species as a polymerization initiation point).

[0045] The free radical generator is not particularly limited, and an organic peroxide is preferably used. The organic peroxide is not particularly limited, and examples thereof include peroxides such as di-tert-butyl peroxyphthalate, tert-butyl hydroperoxide, diisopropylbenzene peroxide, benzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxytrimethylacetate, methyl ethyl ketone peroxide, di-tert-butyl peroxide, and lauroyl peroxide; and azonitriles such as azobisisobutyronitrile and azobisisopropionitrile.

[0046] <Multifunctional polyisocyanate curing agent (B)>

[0047] The polyfunctional polyisocyanate curing agent (B) used in the present invention is not particularly limited as long as it is a polyisocyanate having two or more isocyanate groups in one molecule, and known diisocyanates and compounds derived therefrom can be preferably used.

[0048] For example, diisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, bis(4-isocyanate cyclohexyl)methane, or hydrogenated diphenylmethane diisocyanate can be cited. Further, compounds derived from the aforementioned diisocyanates can be cited, that is, isocyanurate bodies, adducts, biuret-type, uretdione bodies, allophanate bodies, prepolymers (oligomers obtained from diisocyanates and polyols) having isocyanate residues, or their complexes, etc. These can be used alone or in any combination of two or more.

[0049] In addition, a compound obtained by reacting a part of the isocyanate groups of the above-mentioned isocyanate compounds with a compound reactive with the isocyanate group can also be used as a polyfunctional isocyanate curing agent. The compound reactive with the isocyanate group can be exemplified by compounds containing amino groups such as butylamine, hexylamine, octylamine, 2-ethylhexylamine, dibutylamine, ethylenediamine, benzylamine, and aniline; compounds containing hydroxyl groups such as methanol, ethanol, propanol, isopropanol, butanol, hexanol, octanol, 2-ethylhexanol, dodecyl alcohol, ethylene glycol, propylene glycol, benzyl alcohol, and phenol; compounds containing epoxy groups such as allyl glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and cyclohexanedimethanol diglycidyl ether; compounds containing carboxylic acids such as acetic acid, butyric acid, hexanoic acid, octanoic acid, succinic acid, adipic acid, sebacic acid, and phthalic acid.

[0050] As the polyfunctional polyisocyanate curing agent (B) used in the present invention, those having an isocyanurate form of the above-mentioned diisocyanate are preferred because of excellent electrolyte resistance.

[0051] The mixing amount of the multifunctional polyisocyanate curing agent (B) used in the present invention is preferably in the range of 0.5 to 40 parts by mass, more preferably 1 to 35 parts by mass, further preferably 2 to 30 parts by mass, and particularly preferably 3 to 25 parts by mass, relative to 100 parts by mass of the acid-modified polyolefin (A). When it is less than the above value, there is a case where a sufficient curing effect cannot be obtained, and the adhesion and chemical resistance are low. Exceeding the above range, there is a case where the applicability and adhesion are reduced, and in addition, there is a case where pinholes are generated during molding due to reduced tracking. Further from the viewpoint of cost, it is not preferred.

[0052] <Organic Solvent (C)>

[0053] The organic solvent (C) used in the present invention is not particularly limited as long as it is a substance that can dissolve the acid-modified polyolefin (A) and the multifunctional polyisocyanate curing agent (B). Specifically, for example, aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane, heptane, octane, and decane; alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, and ethylcyclohexane; halogenated hydrocarbons such as trichloroethylene, dichloroethylene, chlorobenzene, and chloroform; alcohol solvents such as methanol, ethanol, isopropanol, butanol, pentanol, hexanol, propylene glycol, and phenol; acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, hexanone, cyclohexanone, and isophorone. , acetophenone and other ketone solvents; celluloses such as methyl cellulose and ethyl cellulose; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, methyl propionate, butyl formate; ethylene glycol mono-n-butyl ether, ethylene glycol mono-isobutyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-isobutyl ether, triethylene glycol mono-n-butyl ether, tetraethylene glycol mono-n-butyl ether and other glycol ether solvents, etc., these can be used alone or in combination of two or more.

[0054] The organic solvent (C) is preferably in the range of 80 to 2000 parts by mass relative to 100 parts by mass of the acid-modified polyolefin (A). It is more preferably in the range of 90 to 1600 parts by mass, further preferably in the range of 100 to 1200 parts by mass, and particularly preferably in the range of 110 to 800 parts by mass. When it is less than the above range, the solution state and the shelf life may be reduced, and when it exceeds the above range, the productivity, manufacturing cost, and transportation cost of the laminate and the LiB packaging material containing the laminate may become disadvantageous.

[0055] From the viewpoint of the solution state and the shelf life of the adhesive composition, the organic solvent (C) is preferably a mixed solution of one or more solvents (C1) selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons and halogenated hydrocarbons and one or more solvents (C2) selected from the group consisting of alcohol solvents, ketone solvents, ester solvents and glycol ether solvents. The mixing ratio is preferably in the range of solvent (C1) / solvent (C2) = 50 to 97 / 50 to 3 (mass ratio), more preferably 55 to 95 / 45 to 5 (mass ratio), further preferably 60 to 90 / 40 to 10 (mass ratio), and particularly preferably 70 to 80 / 30 to 20 (mass ratio). When out of the above range, the solution state and shelf life of the adhesive composition may be reduced. In addition, it is particularly preferred that the solvent (C1) is an aromatic hydrocarbon or an alicyclic hydrocarbon, and the solvent (C2) is a ketone solvent.

[0056] <Adhesive Composition>

[0057] The adhesive composition of the present invention is a mixture of the aforementioned acid-modified polyolefin (A), a polyfunctional polyisocyanate curing agent (B) and an organic solvent (C), wherein the acid-modified polyolefin (A) and the curing agent (B) may be dissolved in the organic solvent (C) or dispersed in the organic solvent (C). From the viewpoint of pot life, it is preferred that the acid-modified polyolefin (A) and the curing agent (B) are dissolved in the organic solvent (C).

[0058] The adhesive composition of the present invention, in addition to the aforementioned acid-modified polyolefin (A), multifunctional polyisocyanate curing agent (B) and organic solvent (C), can also be mixed and used with various tackifiers, thermoplastic elastomers, and plasticizers within the scope of not impairing the performance of the present invention. Tackifiers are not particularly limited, and examples thereof include polyterpene resins, rosin resins, aliphatic petroleum resins, alicyclic petroleum resins, copolymerized petroleum resins, and hydrogenated petroleum resins. In addition, thermoplastic elastomers include styrene elastomers such as styrene-ethylene-butylene-styrene copolymer resins and styrene-ethylene-propylene-styrene; olefin elastomers such as ethylene-propylene copolymer resins, ethylene-butylene copolymer resins, ethylene-vinyl acetate copolymer resins, and ethylene-ethyl acrylate copolymer resins. Further, plasticizers preferably include liquid rubbers such as polyisoprene and polybutene, processing oils, and the like. In addition, these tackifiers, thermoplastic elastomers, and plasticizers can be used alone or in combination of two or more.

[0059] The adhesive composition of the present invention may use various curing agents in addition to the aforementioned acid-modified polyolefin (A), multifunctional polyisocyanate curing agent (B) and organic solvent (C) within the scope of not impairing the performance of the present invention. The curing agent is not particularly limited, and examples thereof include epoxy resins, carbodiimide compounds, oxazoline compounds, coupling agents, and the like. Examples of epoxy resins include glycidyl hexahydrophthalate, glycidyl dimer acid glycidyl esters, alicyclic or aliphatic epoxides such as triglycidyl isocyanurate, 3,4-epoxycyclohexylmethyl formate, epoxidized polybutadiene, and epoxidized soybean oil, glycidyl ether type epoxy resins, or glycidylamine type epoxy resins, and the like. In addition, examples of the carbodiimide compound include monocarbodiimide compounds such as dimethylcarbodiimide, diisopropylcarbodiimide, dicyclohexylcarbodiimide, tert-butylisopropylcarbodiimide, diphenylcarbodiimide, and di-β-naphthylcarbodiimide; or polycarbodiimide compounds that can be produced by subjecting an organic diisocyanate such as an aliphatic diisocyanate, an aromatic diisocyanate, or an alicyclic diisocyanate to a decarboxylation condensation reaction in the presence of a condensation catalyst in a solvent-free or inert solvent. In addition, examples of oxazoline compounds include monooxazoline compounds such as 2-oxazoline, 2-methyl-2-oxazoline, 2-phenyl-2-oxazoline, 2,5-dimethyl-2-oxazoline, or 2,4-diphenyl-2-oxazoline; and dioxazoline compounds such as 2,2'-(1,3-phenylene)-bis(2-oxazoline), 2,2'-(1,2-ethylene)-bis(2-oxazoline), 2,2'-(1,4-butylene)-bis(2-oxazoline), or 2,2'-(1,4-phenylene)-bis(2-oxazoline). In addition, examples of coupling agents include silane coupling agents, titanate coupling agents, and the like.

[0060] The adhesive composition of the present invention may be mixed with and used a curing accelerator in addition to the aforementioned acid-modified polyolefin (A), the polyfunctional polyisocyanate curing agent (B) and the organic solvent (C) within the range that does not impair the performance of the present invention. The curing accelerator is not particularly limited, and examples thereof include carboxylic acid metal salts, tertiary amines, quaternary ammonium salts, organic peroxides, hydrazine compounds, metal chelate compounds, phosphorus-containing compounds, and alkaline vulcanizing agents. Examples of the aforementioned carboxylic acid metal salts include metal salts of carboxylic acids having 1 to 30 carbon atoms. Examples of the carboxylic acid constituting the carboxylic acid metal salt include aliphatic carboxylic acids such as acetic acid, butyric acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, behenic acid, octenic acid, erucic acid, elaidic acid, adipic acid, malonic acid, succinic acid, glutaric acid, citric acid, tartaric acid, malic acid, and diglycolic acid; aromatic carboxylic acids such as benzoic acid, chlorobenzoic acid, anisic acid, aminobenzoic acid, phthalic acid, terephthalic acid, naphthoic acid, naphthalenedicarboxylic acid, and benzenetricarboxylic acid; cycloalkane acid; pyruvic acid, etc. In addition, examples of the metal constituting the carboxylic acid metal salt include Li, Na, K, Mg, Ca, Zn, Al, Cu, Pb, Co, Fe, Mn, Sn, and Ti. Specific examples of the carboxylic acid metal salt include lithium acetate, sodium acetate, magnesium acetate, aluminum acetate, potassium butyrate, calcium butyrate, zinc butyrate, sodium octanoate, calcium octanoate, potassium caprate, magnesium caprate, zinc caprate, lithium laurate, sodium laurate, calcium laurate, aluminum laurate, potassium myristate, sodium myristate, aluminum myristate, sodium palmitate, zinc palmitate, magnesium palmitate, sodium stearate, potassium stearate, calcium stearate, zinc stearate, sodium oleate, and behenate. The metal salt of carboxylic acid may be sodium laurate, sodium benzoate, zinc benzoate, sodium phthalate, aluminum phthalate, magnesium terephthalate, calcium naphthalene dicarboxylate, dibutyltin laurate, tributyltin laurate, dioctyltin laurate, tributyltin acetate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin 2-ethylhexanoate, tetrabutyl titanate, tetraisobutyl titanate, tetra-2-ethylhexyl titanate, cobalt naphthenate, copper naphthenate, magnesium naphthenate, cobalt acetoacetate, etc. Among these, preferably lithium laurate, sodium laurate, calcium laurate, aluminum laurate, potassium myristate, sodium myristate, aluminum myristate, sodium palmitate, zinc palmitate, magnesium palmitate, sodium stearate, potassium stearate, calcium stearate, zinc stearate, sodium oleate. In addition, as the metal salt of carboxylic acid, a polymer having a carboxylic acid metal salt structure may also be used. Such polymers include those having a structure obtained by copolymerizing ethylene with a salt of a metal of Group IA, Group IIA, Group IIB, or Group IIIB (e.g., Li, Na, K, Mg, Ca, Zn, Al, etc.) of a radical polymerizable carboxylic acid; and those having a structure obtained by copolymerizing ethylene, a metal salt of a radical polymerizable carboxylic acid, other radical polymerizable carboxylic acids, and / or their derivatives. In addition, examples of the aforementioned tertiary amines include dimethylaniline, triethanolamine, and dimethyl-p-toluidine. In addition, examples of the aforementioned hydrazine compound include 1-acetyl-2-phenylhydrazine.In addition, examples of the metal chelate compound include vanadium acetylacetonate, etc. In addition, examples of the phosphorus-containing compound include dimethylphosphine, triphenylphosphine, etc. In addition, examples of the alkaline vulcanizing agents include hexamethylenetetramine, n-butylaldehyde-aniline condensate, etc.

[0061] The adhesive composition of the present invention may be mixed with and used various additives in addition to the aforementioned acid-modified polyolefin (A), polyfunctional polyisocyanate curing agent (B) and organic solvent (C) within the range that does not impair the performance of the present invention. The additives are not particularly limited, and preferably flame retardants, pigments, anti-blocking agents, etc. are used.

[0062] <Laminate>

[0063] The laminate of the present invention is obtained by laminating a polyolefin resin substrate and a metal substrate using the adhesive composition of the present invention.

[0064] The lamination method can utilize the known lamination manufacturing technology in the past. For example, the adhesive composition can be applied on the surface of the metal substrate using a suitable coating tool such as a roll coater or a coating rod and dried, and there is no particular limitation. After drying, during the period when the adhesive composition layer (adhesive layer) formed on the surface of the metal substrate is in a molten state, on its coating surface, the polyolefin resin substrate is laminated and bonded (laminated bonding) to obtain a laminate.

[0065] The thickness of the adhesive layer formed from the adhesive composition is not particularly limited, but is preferably 0.5 to 10 μm, more preferably 0.8 to 9.5 μm, and even more preferably 1 to 9 μm.

[0066] <Polyolefin resin base material>

[0067] As the polyolefin resin substrate, it is sufficient to appropriately select from the polyolefin resins known in the past. For example, polyethylene, polypropylene, ethylene-propylene copolymer, etc. can be used without particular limitation. Among them, it is preferred to use an unstretched film of polypropylene (hereinafter also referred to as CPP). Its thickness is not particularly limited, preferably 20 to 100 μm, more preferably 25 to 95 μm, and further preferably 30 to 90 μm. In addition, pigments and various additives can be mixed into the polyolefin resin substrate as needed, and surface treatment can also be implemented.

[0068] <Metal substrate>

[0069] The metal substrate is not particularly limited, and for example, various metals such as aluminum, copper, steel, chromium, zinc, duralumin, and die castings and their alloys can be used. In addition, the shape can be any shape such as metal foil, rolled steel plate, flat plate, tube, can, lid, etc. Generally speaking, aluminum foil is preferred from the viewpoint of processability. In addition, it varies depending on the purpose of use, and is generally used in the form of a sheet with a thickness of 0.01 to 10 mm, preferably 0.02 to 5 mm.

[0070] Furthermore, the surfaces of these metal substrates may be previously treated or may be left untreated. In either case, the same effects can be achieved.

[0071] [Example]

[0072] The present invention is described in more detail below with reference to the following examples. However, the present invention is not limited to the examples. In the examples and comparative examples, parts are simply recorded and represent parts by mass.

[0073] <Production Example of Acid-modified Polyolefin (A)>

[0074] Production Example 1

[0075] In a 1L autoclave, 100 parts by mass of a propylene-ethylene copolymer (storage modulus at 25°C: 320 MPa, tensile elongation at break at 25°C: 760%), 233 parts by mass of toluene, 1 part by mass of maleic anhydride, and 0.5 parts by mass of di-tert-butyl peroxide were added, heated to 140°C, and further stirred for 1 hour (hereinafter referred to as "reaction" for 1 hour). Thereafter, the obtained reaction solution was cooled to 100°C, and then injected into a container containing 717 parts by mass of toluene and 950 parts by mass of methyl ethyl ketone preheated to 40°C while stirring, cooled to 40°C, stirred for 30 minutes, and further cooled to 25°C to precipitate a resin (hereinafter, the operation of injecting the reaction solution into a solvent such as methyl ethyl ketone while stirring and cooling to precipitate the resin is referred to as "reprecipitation"). Thereafter, the slurry containing the resin is centrifuged to separate the acid-modified propylene-ethylene copolymer graft-polymerized with maleic anhydride from the (poly)maleic anhydride and low molecular weight substances.

[0076] Furthermore, the acid-modified propylene-ethylene copolymer removed by centrifugation was added to a container previously kept at 25° C. and filled with 2000 parts by mass of methyl ethyl ketone while stirring, and the stirring was continued for 1 hour. Thereafter, the slurry was centrifuged to further separate the acid-modified propylene-ethylene copolymer from (poly)maleic anhydride and low molecular weight substances. This operation was repeated twice to purify (herein, the operation of adding the acid-modified propylene-ethylene copolymer removed by centrifugation to methyl ethyl ketone while stirring and centrifuging again to strengthen purification is referred to as "re-slurrying").

[0077] After purification, the product was dried at 70°C for 5 hours under reduced pressure to obtain a maleic anhydride-modified propylene-ethylene copolymer (PO-1, acid value 2 mgKOH / g resin, acetone extractable component ratio 0.1% by mass, storage modulus 300 MPa at 25°C, tensile elongation at break 600% at 25°C, weight average molecular weight 190,000, Tm 88°C, ΔH 37 J / g) as an acid-modified polyolefin.

[0078] Production Example 2

[0079] The same procedure as in Preparation Example 1 was followed except that the amount of maleic anhydride added was changed to 3 parts by mass, the number of repulpings was changed to 1 time, and the amount of methyl ethyl ketone added during repulping was changed to 1000 parts by mass, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-2, acid value 5 mgKOH / g resin, acetone extractable component ratio 1.8% by mass, storage modulus at 25°C 280 MPa, tensile elongation at break at 25°C 650%, weight average molecular weight 180,000, Tm 88°C, ΔH 36 J / g) as an acid-modified polyolefin.

[0080] Production Example 3

[0081] The same procedure as in Preparation Example 1 was carried out except that the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 40 parts by mass, the amount of di-tert-butyl peroxide added was changed to 8 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, and the number of reslurrying was changed to 5 times. Thus, a maleic anhydride-modified propylene-ethylene copolymer (PO-3, acid value 48 mgKOH / g resin, acetone extractable component ratio 0.1% by mass, storage modulus at 25°C 180 MPa, tensile elongation at break at 25°C 350%, weight average molecular weight 31,000, Tm 85°C, ΔH 31 J / g) as an acid-modified polyolefin was obtained.

[0082] Production Example 4

[0083] The same procedure as in Preparation Example 1 was carried out except that the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 40 parts by mass, the amount of di-tert-butyl peroxide added was changed to 8 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurry was changed to 3 times, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-4, acid value 48 mgKOH / g resin, acetone extractable component ratio 1.8 mass%, storage modulus at 25°C 150 MPa, tensile elongation at break at 25°C 300%, weight average molecular weight 27,000, Tm 85°C, ΔH 30 J / g) as an acid-modified polyolefin.

[0084] Production Example 5

[0085] The same procedure as in Preparation Example 1 was carried out except that the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 20 parts by mass, the amount of di-tert-butyl peroxide added was changed to 6 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurry was changed to 2 times, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-5, acid value 25 mgKOH / g resin, acetone extractable component ratio 0.9 mass%, storage modulus at 25°C 400 MPa, tensile elongation at break at 25°C 500%, weight average molecular weight 60,000, Tm 87°C, ΔH 35 J / g) as an acid-modified polyolefin.

[0086] Production Example 6

[0087] The same procedures as in Preparation Example 1 were carried out except that the amount of the propylene-ethylene copolymer (storage modulus at 25° C.: 52 MPa, tensile elongation at break at 25° C.: 1050%) was changed to 100 parts by mass, the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 30 parts by mass, the amount of di-tert-butyl peroxide added was changed to 6 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurry was changed to 2 times, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-6, acid value: 25 mgKOH / g resin, acetone extractable component ratio: 1.0% by mass, storage modulus at 25° C.: 12 MPa, tensile elongation at break at 25° C.: 900%, weight average molecular weight: 60,000, Tm: 58° C., ΔH: 7 J / g) as an acid-modified polyolefin.

[0088] Production Example 7

[0089] The same procedures as in Preparation Example 1 were carried out except that the amount of the propylene homopolymer (storage modulus at 25°C: 2100 MPa, tensile elongation at break at 25°C: 900%) was changed to 100 parts by mass, the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 30 parts by mass, the amount of di-tert-butyl peroxide added was changed to 6 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurry was changed to 2 times. Thus, a maleic anhydride-modified propylene homopolymer (PO-7, acid value: 25 mgKOH / g resin, acetone extractable component ratio: 0.9% by mass, storage modulus at 25°C: 1800 MPa, tensile elongation at break at 25°C: 60%, weight average molecular weight: 60,000, Tm: 85°C, ΔH: 5 J / g) as an acid-modified polyolefin was obtained.

[0090] Production Example 8

[0091] The same procedures as in Preparation Example 1 were carried out except that the amount of the propylene-ethylene copolymer (storage modulus at 25°C: 2720 MPa, tensile elongation at break at 25°C: 400%) was changed to 100 parts by mass, the amount of toluene added was changed to 186 parts by mass, the amount of maleic anhydride added was changed to 20 parts by mass, the amount of di-tert-butyl peroxide added was changed to 6 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurry was changed to 2 times, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-8, acid value: 25 mgKOH / g resin, acetone extractable component ratio: 1.0% by mass, storage modulus at 25°C: 2350 MPa, tensile elongation at break at 25°C: 38%, weight average molecular weight: 60,000, Tm: 125°C, ΔH: 63 J / g) as an acid-modified polyolefin.

[0092] Production Example 9

[0093] The same procedure as in Preparation Example 1 was carried out except that the amount of toluene added was changed to 186 parts by mass, the amount of maleic anhydride added was changed to 20 parts by mass, the amount of di-tert-butyl peroxide added was changed to 6 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 1200 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1200 parts by mass of methyl ethyl ketone, and the number of reslurry was changed to 2 times, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-9, acid value 25 mgKOH / g resin, acetone extractable component ratio 1.2 mass%, storage modulus at 25°C 7 MPa, tensile elongation at break at 25°C 1200%, weight average molecular weight 60,000, no Tm peak, ΔH OJ / g) as an acid-modified polyolefin.

[0094] Production Example 10

[0095] The same procedures as in Preparation Example 1 were carried out except that the amount of the propylene-ethylene copolymer (storage modulus at 25° C.: 500 MPa, tensile elongation at break at 25° C.: 680%) was changed to 100 parts by mass, the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 0.5 parts by mass, the amount of di-tert-butyl peroxide added was changed to 0.2 parts by mass, the reaction time was changed to 1 hour, the solvent used for reprecipitation was changed to 1000 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurry was changed to 2 times. Thus, a maleic anhydride-modified propylene-ethylene copolymer (PO-10, acid value: 1 mgKOH / g resin, acetone extractable component ratio: 0.1% by mass, storage modulus at 25° C.: 400 MPa, tensile elongation at break at 25° C.: 600%, weight average molecular weight: 65,000, Tm: 71° C., ΔH: 35 J / g) as an acid-modified polyolefin was obtained.

[0096] Production Example 11

[0097] The same procedure as in Preparation Example 1 was carried out except that the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 50 parts by mass, the amount of di-tert-butyl peroxide added was changed to 10 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurry times was changed to 3 times, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-11, acid value 55 mgKOH / g resin, acetone extractable component ratio 1.0 mass%, storage modulus at 25°C 150 MPa, tensile elongation at break at 25°C 320%, weight average molecular weight 30,000, Tm 83°C, ΔH 25 J / g) as an acid-modified polyolefin.

[0098] Production Example 12

[0099] The same procedure as in Preparation Example 1 was carried out except that the amount of toluene added was changed to 150 parts by mass, the amount of maleic anhydride added was changed to 40 parts by mass, the amount of di-tert-butyl peroxide added was changed to 8 parts by mass, the reaction time was changed to 3 hours, and the number of reslurrying was changed to 3 times, thereby obtaining a maleic anhydride-modified propylene-ethylene copolymer (PO-12, acid value 46 mgKOH / g resin, acetone extractable component ratio 4.5% by mass, storage modulus at 25°C 110 MPa, tensile elongation at break at 25°C 90%, weight average molecular weight 35,000, Tm 86°C, ΔH 30 J / g) as an acid-modified polyolefin.

[0100] (Preparation of main agent 1)

[0101] In a 500 ml four-necked flask equipped with a water-cooled reflux condenser and a stirrer, 100 parts by mass of the maleic anhydride-modified propylene-ethylene copolymer (PO-1) obtained in Preparation Example 1, 280 parts by mass of methylcyclohexane and 120 parts by mass of methyl ethyl ketone were added, and the temperature was raised to 80° C. while stirring, and the stirring was continued for 1 hour and then cooled to obtain a main agent 1. The solution state is shown in Table 1.

[0102] (Preparation of main agents 2 to 19)

[0103] Main compositions 2 to 19 were prepared in the same manner as in Main composition 1, with the acid-modified polyolefin and the organic solvent being changed as shown in Table 1. Table 1 shows the mixing amounts and solution states.

[0104] [Table 1]

[0105]

[0106]

[0107] Example 1

[0108] 500 parts by mass of the main agent 1 and 1 part by mass of SUMIDUR (registered trademark) N-3300 as a polyfunctional polyisocyanate curing agent (B) were mixed to obtain an adhesive composition. Table 2 shows the evaluation results of pot life, adhesion, chemical resistance and moldability.

[0109] Examples 2 to 21, Comparative Examples 1 to 3

[0110] Examples 2 to 21 and Comparative Examples 1 to 3 were prepared in the same manner as Example 1, with the main agents 1 to 19 and the curing agents changed as shown in Tables 2 and 3. The results of the mixing amount, pot life, adhesion, chemical resistance and moldability are shown in Tables 2 and 3.

[0111] [Table 2]

[0112]

[0113] [Table 3]

[0114]

[0115] The curing agents used in Tables 2 and 3 are as follows.

[0116] <Multifunctional polyisocyanate curing agent (B)>

[0117] Isocyanurate of hexamethylene diisocyanate: SUMIDUR (registered trademark) N-3300 (manufactured by Bayer AG)

[0118] Biuret form of hexamethylene diisocyanate: DURANATE (registered trademark) 24A-100 (manufactured by Asahi Kasei Chemicals Corporation)

[0119] The acid-modified polyolefins, main agents and adhesive compositions obtained in the above manner were analyzed, measured and evaluated according to the following methods.

[0120] Determination of acid value

[0121] The acid value (mgKOH / g resin) in the present invention refers to the amount of KOH required to neutralize 1 g of the acid-modified polyolefin (A), and is measured according to the test method of JIS K0070 (1992). Specifically, 1 g of the acid-modified polyolefin is dissolved in 100 g of xylene adjusted to 100° C., and then titrated with a 0.1 mol / L potassium hydroxide ethanol solution [trade name "0.1 mol / L ethanolic potassium hydroxide solution", manufactured by Wako Pure Chemical Industries, Ltd.] at the same temperature using phenolphthalein as an indicator. At this time, the amount of potassium hydroxide required for titration is converted into mg to calculate the acid value (mgKOH / g).

[0122] Determination of the ratio of acetone extractable components

[0123] The acetone extractable component ratio in the present invention is measured by refluxing acetone for 2 hours using a Soxhlet extractor. Specifically, it is the following value: 50 g of the acid-modified polyolefin (A) is weighed onto a cylindrical filter paper, placed in a Soxhlet extraction tube, and then a flat-bottomed flask containing 1100 mL of acetone and a cooling tube are assembled, and acetone extraction is performed by refluxing in a water bath for 2 hours. After that, the cylindrical filter paper is removed, and the acetone extract in the flat-bottomed flask is distilled off, and the weight of the residue after drying under reduced pressure at 100°C for 1 hour is further weighed, and the weight is calculated by the following formula.

[0124] Acetone extract component ratio (mass %) = (extraction residue weight / sample collection amount) × 100

[0125] [Measurement of storage modulus (E') at 25°C]

[0126] The storage modulus (E') in the present invention is measured according to the test method of JIS K7244-4 (1999). Specifically, it is a value obtained by measuring the temperature at a frequency of 10 Hz from -50°C at a rate of 5°C / min using a dynamic viscoelasticity measuring apparatus DVA-200 manufactured by IT Instruments.

[0127] [Determination of tensile elongation at break (Eb) at 25°C]

[0128] The tensile elongation at break (Eb) in the present invention is measured according to the test method of JIS K7161 (2014). Specifically, it is a value obtained by measuring the elongation (%) at break by stretching at a speed of 50 mm / min at 25°C using TENSILON RTM-100 manufactured by Oriental Corporation.

[0129] [Measurement of weight average molecular weight (Mw)]

[0130] The weight average molecular weight in the present invention is a value measured using a gel permeation chromatograph Alliance e2695 manufactured by Waters Corporation of Japan (hereinafter referred to as GPC, standard substance: polystyrene resin, mobile phase: tetrahydrofuran, chromatographic column: Shodex KF-806 + KF-803, chromatographic column temperature: 40°C, flow rate: 1.0 ml / min, detector: photodiode array detector (wavelength 254 nm = ultraviolet light)).

[0131] [Determination of melting point and heat of fusion]

[0132] The melting point and heat of fusion in the present invention are values ​​measured by using a differential scanning calorimeter (hereinafter referred to as DSC, manufactured by TA Instrument Japan, Q-2000), heating at a rate of 20°C / min to melt, cooling to resinify, and heating again to melt, and the top temperature and area of ​​the melting peak.

[0133] [Evaluation of main agent solution status]

[0134] The solution states of the main agents 1 to 19 were evaluated by measuring the solution viscosity at 25° C. using a Brookfield viscometer TVB-10M (hereinafter also referred to as a B-type viscometer) manufactured by Toki Sangyo Co., Ltd.

[0135] <Evaluation Criteria>

[0136] ◎(Excellent in practical application): less than 500mPa·s

[0137] ○(Practical): 500mPa·s or more, less than 1000mPa·s

[0138] × (Not applicable): Viscosity cannot be measured due to gelation or above 1000 mPa·s

[0139] Evaluation of applicability

[0140] The pot life refers to the stability of the solution immediately after or after a certain period of time after the crosslinking agent or curing agent is mixed with the acid-modified polyolefin. Good pot life means that the viscosity of the solution increases little and can be stored for a long time; poor pot life means that the viscosity of the solution increases (thickening), and in severe cases, gelation occurs, making it difficult to apply to the substrate and unable to be stored for a long time.

[0141] The pot life of the adhesive compositions obtained in Examples 1 to 21 and Comparative Examples 1 to 3 was evaluated by measuring the solution viscosity at 25° C. using a B-type viscometer after storage at 25° C. and 40° C. for 24 hours. The evaluation results are shown in Tables 2 and 3.

[0142] <Evaluation Criteria>

[0143] ◎(Excellent in practical application): less than 500mPa·s

[0144] ○(Practical): 500mPa·s or more, less than 1000mPa·s

[0145] × (Not applicable): Viscosity cannot be measured due to gelation or above 1000 mPa·s

[0146] Preparation of laminated body of metal substrate and polyolefin resin substrate

[0147] Aluminum foil (8079-0 manufactured by Sumigaru Aluminum Foil Co., Ltd., thickness 40 μm) was used as the metal substrate, and unstretched polypropylene film (Pylen (registered trademark) film CT manufactured by Toyobo Co., Ltd., thickness 40 μm) (hereinafter also referred to as CPP) was used as the polyolefin resin substrate.

[0148] The adhesive composition obtained in Examples 1 to 21 and Comparative Examples 1 to 3 was applied to a metal substrate using a coating rod, and the thickness of the adhesive layer after drying was adjusted to 3 μm. The coated surface was dried for 1 minute in an atmosphere of 100°C using a warm air dryer to obtain a metal substrate laminated with an adhesive layer having a thickness of 3 μm. A polyolefin resin substrate was overlapped on the surface of the adhesive layer, and a small desktop test laminator (SA-1010-S) manufactured by TESTER SANGYO was used, with a lamination temperature of 80°C or 120°C, at 0.3 MPa and 1 m / min, and the laminate was aged at 25°C and 50% RH for 36 hours to obtain a laminate.

[0149] The laminated body obtained in the above manner was evaluated by the following methods.

[0150] Evaluation of Adhesion

[0151] Cut the above-mentioned laminated form into a size of 100 mm × 15 mm, and evaluate the adhesiveness according to the following criteria by using the T-peel test. The evaluation results are shown in Tables 2 and 3.

[0152] <T-peel test>

[0153] According to the test method of ASTM-D1876-61, use TENSILON RTM-100 manufactured by Orientic Coporation to measure the peel strength at a tensile speed of 50 mm / min in an atmosphere of 25°C. The average value of 5 test values is taken for the peel strength (N / cm) between the metal substrate and the polyolefin resin substrate.

[0154] ☆ (Particularly excellent in practical use): 8.0 N / cm or more or material breakage of CPP occurs (hereinafter also simply referred to as "material breakage"). Material breakage means that peeling does not occur at the interface between the metal substrate and CPP, but the metal substrate or CPP is damaged.

[0155] ◎ (Excellent in practical use): 7.5 N / cm or more and less than 8.0 N / cm

[0156] 〇 (Practicable): 7.0 N / cm or more and less than 7.5 N / cm

[0157] × (Not practicable): Less than 7.0 N / cm

[0158] Evaluation of chemical resistance

[0159] In order to study the usability as a packaging material for LiB, an evaluation of chemical resistance (hereinafter also referred to as electrolyte resistance) using an electrolyte test was carried out. Cut the above-mentioned laminated form into a size of 100 mm × 15 mm, and immerse it in an electrolyte [ethylene carbonate / diethyl carbonate / dimethyl carbonate = 1 / 1 / 1 (volume ratio) added with lithium hexafluorophosphate] at 85°C for 1 day. Then, take out the laminate, wash it with ion-exchanged water, wipe the water with a wiping paper, and dry the water thoroughly, and evaluate the chemical resistance according to the following criteria by using the T-peel test. The evaluation results are shown in Tables 2 to 3.

[0160] <Evaluation criteria>

[0161] ☆ (Particularly excellent in practical use): 8.0 N / cm or more or material breakage

[0162] ◎ (Excellent in practical use): 7.5 N / cm or more and less than 8.0 N / cm

[0163] ○ (practical): 7.0 N / cm or more, less than 7.5 N / cm

[0164] ×(Not applicable): less than 7.0N / cm

[0165] Evaluation of formability

[0166] Also, in order to study the usability as a packaging material for LiB, an evaluation of the formability using a deep drawing tester was implemented. The aforementioned laminate was cut into a size of 80×120 mm and cold-formed. Specifically, a stretch forming machine (model: TP-25C-X2) manufactured by AMADA Co., Ltd., a forming mold (female mold) with a diameter of 55 mm×35 mm, and a corresponding forming mold (male mold) were used. The forming depth was changed from a forming depth of 0.5 mm in units of 0.5 mm at a pushing pressure of 0.4 MPa at 25°C. Ten samples (laminates) were cold-formed. For the samples after cold forming, the deepest forming depth in which no wrinkles were generated in any of the 10 samples, and no pinholes or cracks were generated in the aluminum foil was taken as the limit forming depth of the sample. The formability of the battery packaging material was evaluated based on the following criteria based on the limit forming depth. The evaluation results are shown in Tables 2 to 3.

[0167] <Judgment Criteria>

[0168] ☆(Excellent in practical application): Maximum forming depth 6.0mm or more

[0169] ◎(Excellent in practical application): The ultimate forming depth is 4.0 mm or more and less than 6.0 mm

[0170] ○(Practical): Limit forming depth 2.0mm or more and less than 4.0mm

[0171] ×: The maximum forming depth is less than 2.0 mm

[0172] Industrial Applicability

[0173] The adhesive composition of the present invention contains an acid-modified polyolefin, a multifunctional polyisocyanate curing agent and an organic solvent. Even if it is stored for a long time, it will not increase viscosity or gel, can maintain a good shelf life, and can take into account the good adhesion, electrolyte resistance and formability between the metal substrate and the polyolefin resin substrate. Therefore, the laminate of the polyolefin resin substrate and the metal substrate formed by the adhesive composition of the present invention can be used not only in the fields of home appliance outer panels, furniture materials, building interior components, etc., but also can be widely used as a packaging material (pouch form) for lithium batteries used in personal computers, mobile phones, cameras, etc.

Claims

1. An adhesive composition comprising an acid-modified polyolefin A, a multifunctional polyisocyanate curing agent B and an organic solvent C, wherein the acid value of the acid-modified polyolefin A is 2 to 50 mgKOH / g resin, the acetone extractable component ratio of the acid-modified polyolefin A is greater than 0.1 and less than 2% by mass, the storage modulus E' of the acid-modified polyolefin A at 25° C. is in the range of 10 to 2000 MPa, the tensile elongation at break Eb of the acid-modified polyolefin A at 25° C. is in the range of 50% to 1000%, and the weight average molecular weight Mw of the acid-modified polyolefin A is 50,000 to 200,000; The adhesive composition contains 0.5 to 40 parts by mass of a polyfunctional polyisocyanate curing agent B and 80 to 2000 parts by mass of an organic solvent C, relative to 100 parts by mass of the acid-modified polyolefin A. The acid-modified polyolefin A is a product obtained by grafting at least one of α,β-unsaturated carboxylic acid and its anhydride to at least one of polyethylene, polypropylene and propylene-α-olefin copolymer, and the α-olefin is at least one of ethylene, 1-butene, 1-heptene, 1-octene, 4-methyl-1-pentene and vinyl acetate. The organic solvent C is a mixed liquid of solvent C1 and solvent C2, wherein solvent C1 is one or more solvents selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons and halogenated hydrocarbons, and solvent C2 is one or more solvents selected from the group consisting of alcohol solvents, ketone solvents, ester solvents and glycol ether solvents, and in terms of mass ratio, solvent C1 / solvent C2=50~97 / 50~3. 2 . The adhesive composition according to claim 1 , which is used for bonding a polyolefin resin substrate to a metal substrate. 3 . The adhesive composition according to claim 1 , wherein the acid-modified polyolefin A is an acid-modified propylene-α-olefin copolymer, and the propylene component of the propylene-α-olefin copolymer is 50 mol % or more.

4. The adhesive composition according to claim 1 or claim 2, wherein the acid-modified polyolefin A is acid-modified with an α,β-unsaturated carboxylic acid and an anhydride thereof, and the α,β-unsaturated carboxylic acid and an anhydride thereof is at least one of maleic acid, itaconic acid, citraconic acid and anhydrides thereof. 5 . The adhesive composition according to claim 1 , wherein the weight average molecular weight (Mw) of the acid-modified polyolefin (A) is in the range of 50,000 to 110,000. 6 . The adhesive composition according to claim 1 , wherein the acid-modified polyolefin A is crystalline and has a melting point Tm in the range of 50° C. to 120° C. 7 . The adhesive composition according to claim 1 , wherein the heat of fusion ΔH of the acid-modified polyolefin A is in the range of 1 J / g to 60 J / g. 8 . A laminate of a polyolefin resin substrate and a metal substrate bonded together with the adhesive composition according to claim 1 .

9. A lithium ion battery packaging material comprising the laminate according to claim 8 as a constituent member.

Citation Information

Patent Citations

  • Lithium cell

    JP2001243928A

  • Packaging material for lithium ion battery and manufacturing method thereof

    JP2002216714A

  • Packing material for cell, and cell using the same

    JP2003031188A

  • Laminated body and packaging material

    JP2004042477A

  • Outer package for battery, and battery

    JP2009238475A

Cited By

  • Pressure-sensitive adhesive composition, pressure-sensitive adhesive, preparation method of pressure-sensitive adhesive, adhesive tape and application

    CN121471844A